2015
DOI: 10.1182/blood-2014-10-602060
|View full text |Cite
|
Sign up to set email alerts
|

Premature changes in trabecular and cortical microarchitecture result in decreased bone strength in hemophilia

Abstract: Key Points Patients with hemophilia have abnormal bone microarchitecture and decreased biomechanical bone strength compared with normal healthy controls. Decreased BMD and bone strength are associated with severity of hemophilic arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Our HJHS includes also the operated joints, because studies that have investigated the impact of osteoarthritis on gait demonstrated that the arthritic knee influences the movement of hip and trunk, and how the prosthesis improves the movement . As regards bone mass, our data agree with studies of other populations, showing a relation between haemophilia and reduced BMD, in particular at peripheral skeletal sites . In haemophilic patients, different factors can lead to low BMD, like reduced physical activity, infections such as HIV and HCV, low vitamin D levels, low BMI and hypogonadism.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our HJHS includes also the operated joints, because studies that have investigated the impact of osteoarthritis on gait demonstrated that the arthritic knee influences the movement of hip and trunk, and how the prosthesis improves the movement . As regards bone mass, our data agree with studies of other populations, showing a relation between haemophilia and reduced BMD, in particular at peripheral skeletal sites . In haemophilic patients, different factors can lead to low BMD, like reduced physical activity, infections such as HIV and HCV, low vitamin D levels, low BMI and hypogonadism.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding bone quality, our patients presented a TBS within the normal range for age classes, appearing below the threshold for risk fracture (1.200) only in the oldest age class. This result could indicate that in haemophilia vertebral microarchitecture seems to be not deranged as that of peripheral skeletal sites, as demonstrated by pQCT by Lee et al Another possible explanation could be that TBS and BS, like pQCT, are not able to detect very small derangements of trabecular microarchitecture. Moreover, TBS did not correlate with HJHS.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, a recent study showed that both low trabecular and cortical BMD exist in PWH . These microarchitectural deficits translate into a relatively low biomechanical bone strength and may in part account for the increased fracture risk in these patients, irrespectively of BMD . However, a study in children with haemophilia did not show differences in trabecular or cortical volumetric BMD compared with the age‐specific reference values, after adjustment for patients’ shorter body height .…”
Section: Introductionmentioning
confidence: 98%
“…Low lumbar spine BMD seems to be prevalent in PWH with a fracture history, although vertebral fractures are uncommon , reflecting perhaps deficits in trabecular bone in these patients. Interestingly, a recent study showed that both low trabecular and cortical BMD exist in PWH . These microarchitectural deficits translate into a relatively low biomechanical bone strength and may in part account for the increased fracture risk in these patients, irrespectively of BMD .…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral quantitative computed tomography has already been employed for the assessment of osteoporosis in both children and adults PWH. Nonetheless, in these studies, the impact of multiple joint bleeds in the bone properties of the target‐joints has not been investigated.…”
Section: Introductionmentioning
confidence: 99%